Pengaruh Komitmen, Motivasi Dan Budaya Kerja Terhadap Kinerja Pegawai Kantor Kecamatan Arjasa Kabupaten Sumenep - Ahmad Fajri; Nur Hidayati; Ita Athia (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This examination is directed to determine the impact of the impact of responsibility, inspiration, and work culture on the presentation of representatives at the Arjasa District Office, Sumenep Regency. This research uses research with quantitative methodology. The strategy used in this study was multiple direct relapse examinations with the help of the SPSS 20 program and using the immersion test of 36 people.The consequence of this research is that the overall responsibility, inspiration, and work culture have a significant effect on the presentation of representatives at the Arjasa District Office, Sumenep Regency. Keywords: Commitment, Motivation, Work Culture and Employee Performance.